Strategic Human Resource Management in Social Enterprises: A Systematic Review of Practices and Challenges - Fanji Wijaya; Syamsul Hadi Senen (Research Synergy Foundation, 2024)
Strategic Human Resource Management (SHRM) has evolved to align human resource practices with organizational objectives to enhance performance and create competitive advantages. This study reviews the application of SHRM in social enterprises (SEs) that balance social impact and financial sustainability. A systematic review methodology was used to identify and analyze various SHRM practices implemented in social enterprises, as well as to evaluate the challenges faced by the sector. This study explored the scientific literature by analyzing strategic HRM in social enterprises using bibliometrics. The researcher then conducted keywords on the Scopus database (Scopus.com). The analysis results showed that 261,499 articles were collected. The researcher used Program R to conduct the bibliometric analysis. SEs adopt innovative HR practices like value-based recruitment, tailored training programs, volunteer management, and adaptive performance evaluations to align employee values with organizational missions while promoting inclusivity and retention despite resource constraints. However, SE face challenges such as financial limitations, skill mismatches, high turnover, cultural diversity, and stakeholder pressures. To address these issues, SEs must innovate HR strategies that integrate sustainability and stakeholder expectations. This study highlights an increase in SHRM research within SEs driven by sustainability concerns and the complexity of workforce management. Through thematic analysis, two main clusters emerge: sustainable development and human-organization dimensions, illustrating the link between strategic HR decisions, employee engagement, and organizational outcomes. Despite growth, a decline in citation count suggests the need for better research accessibility, collaboration, and quality. This research emphasizes SHRM’s importance in supporting SEs’ dual missions and managing tensions between social and economic goals. Future research should explore cross-regional dynamics, technology integration, and stakeholder engagement to enhance SHRM’s practical and theoretical contributions and ensure SEs can better achieve sustainable social impact. This study employed a systematic review methodology, collecting data from the existing literature, and conducting thematic analysis to explore trends and gaps in SHRM practices for SEs.